Znamiona państwa wyznaniowego. Uwagi na kanwie dorobku współczesnego konstytucjonalizmu - Borecki, Paweł (Wydawnictwo Naukowe UAM, 2017)
An analysis of contemporary constitutions indicates that the number of denominational states is slowly decreasing. However, we also encounter opposite tendencies. The model of a denominational, or a religious state is primarily characteristic for Muslim countries of the Near and Middle East and for a number of Southeast Asian countries. In the last decades, the number of Christian states and secular ideological states has declined signiﬁ cantly. There is a stable group of states with Buddhism as a privileged religion. The religious constitutional norms of states of confession are generally characterised by a high degree of generality. Detailed provisions are seldom and denominational clauses are primarily included among the principles of the supreme constitution. Underlying the religious character of the state lies the rejection of the neutrality of the worldview. It is not possible, on the basis of the constitution alone, to reconstruct a detailed, universal model of a religious state. In the light of fundamental laws, the most common characteristics of religious states are: the negation of the neutrality of the state in worldviews, the acceptance of a particular religion as the offi cial religion, the rejection of the equality of religious associations, the requirement of a head of state to follow the state religion or belief, and the state support for a given confession. The constitutions of most religious states formally provide for religious freedom. In the fundamental laws of some Muslim states, the guarantees for this freedom are, however, silent. The Western political culture fails the characteristics of an organisational unity of the state or the religious apparatus. The socio-political reality of contemporary religious states indicates that this model of statehood cannot be a priori regarded as contrary to the principles of democracy and human rights.
Characteristics of a denominational state. Some remarks based on the accomplishments of contemporary constitutionalism
Keywords: religious/denominational state; the state; church relationship; contemporary constitutions; freedom of religion – Islam